2008
DOI: 10.1128/jvi.02469-07
|View full text |Cite
|
Sign up to set email alerts
|

Human APOBEC3G Can Restrict Retroviral Infection in Avian Cells and Acts Independently of both UNG and SMUG1

Abstract: APOBEC3 proteins are mammal-specific cytidine deaminases that can restrict retroviral infection. The exact mechanism of the restriction remains unresolved, but one model envisions that uracilated retroviral cDNA, generated by cytidine deamination, is the target of cellular glycosylases. While restriction is unaffected by UNG deficiency, it has been suggested that the SMUG1 glycosylase might provide a backup. We found that retroviral restriction can be achieved by introducing human APOBEC3G into chicken cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 54 publications
2
43
2
Order By: Relevance
“…1 and 2 demonstrated that the recruitment of UNG2 into virions was directly responsible for influencing HIV-1 mutation, we then decided to reevaluate the real influence of UNG2 incorporation into HIV-1 particles on virus infectivity. First, the contradictory results reported in the literature about the impact of UNG2 on HIV-1 infectivity and replication (9,17,18,22,37,40,48) were further challenged using a single-round infection assay for the investigation of virus infectivity when UNG2 was overexpressed in either virus-producing cells or target cells. Wild-type reporter viruses carrying the gene encoding GFP were produced in 293T cells overexpressing the HA-tagged form of UNG2, and equivalent amounts of virus, as measured by HIV-1 CAp24 in ELISA, were used to assay virus infectivity on HeLa cells stably expressing the CD4 receptor (HeLa-CD4).…”
Section: Resultsmentioning
confidence: 99%
“…1 and 2 demonstrated that the recruitment of UNG2 into virions was directly responsible for influencing HIV-1 mutation, we then decided to reevaluate the real influence of UNG2 incorporation into HIV-1 particles on virus infectivity. First, the contradictory results reported in the literature about the impact of UNG2 on HIV-1 infectivity and replication (9,17,18,22,37,40,48) were further challenged using a single-round infection assay for the investigation of virus infectivity when UNG2 was overexpressed in either virus-producing cells or target cells. Wild-type reporter viruses carrying the gene encoding GFP were produced in 293T cells overexpressing the HA-tagged form of UNG2, and equivalent amounts of virus, as measured by HIV-1 CAp24 in ELISA, were used to assay virus infectivity on HeLa cells stably expressing the CD4 receptor (HeLa-CD4).…”
Section: Resultsmentioning
confidence: 99%
“…One well-characterized mechanism is the enzymatic deamination of cytosine in the minus strand of HIV-1 cDNA by members of the APOBEC3 subfamily (APOBEC3D, -F, -G, and -H) to generate C/G→U/A transition mutations after plus strand synthesis (43,44). This deamination mechanism leads to lethal hypermutation of the viral genome and potent restriction of viral infection, but there are conflicting reports as to whether UNG2 excision of uracils is part of the restriction mechanism (45)(46)(47). In contrast, the dUTP-mediated mechanism elaborated here results in nonmutagenic incorporation of uracil on both strands of the viral DNA and requires hUNG2 to prevent viral integration.…”
Section: Discussionmentioning
confidence: 99%
“…First, it may subject the cDNA to DNA repair pathways that could ultimately degrade the viral genome, although it is unclear if classic base excision repair pathways play a role (40). Second, the introduction of deoxyuridine can compromise integration into the host genome (41).…”
Section: Loop Graft Variants Effectively Restrict Hiv-bhagwat and Co-mentioning
confidence: 99%